Reliability and validity analysis of the open-source Chinese Foot and Ankle Outcome Score (FAOS). (June 2018) - Ling, Samuel K.K.; Chan, Vincent; Ho, Karen; Ling, Fona; Lui, T.H.
Highlights: First validated self-reported outcome score for foot and ankle problems in the Chinese language. It is an open source scoring system which can be freely used by everyone without charge. The Chinese FAOS is reliable, internally consistent and correlates positively with standardised scales. Abstract: Aim: Develop the first reliable and validated open-source outcome scoring system in the Chinese language for foot and ankle problems. Methods: Translation of the English FAOS into Chinese following regular protocols. First, two forward-translations were created separately, these were then combined into a preliminary version by an expert committee, and was subsequently back-translated into English. The process was repeated until the original and back translations were congruent. This version was then field tested on actual patients who provided feedback for modification. The final Chinese FAOS version was then tested for reliability and validity. Reliability analysis was performed on 20 subjects while validity analysis was performed on 50 subjects. Tools used to validate the Chinese FAOS were the SF36 and Pain Numeric Rating Scale (NRS). Internal consistency between the FAOS subgroups was measured using Cronbach's alpha. Spearman's correlation was calculated between each subgroup in the FAOS, SF36 and NRS. Results: The Chinese FAOS passed both reliability and validity testing; meaning it is reliable, internally consistent and correlates positively with the SF36 and the NRS. Discussion and conclusions: The Chinese FAOS is a free, open-source scoring system that can be used to provide a relatively standardised outcome measure for foot and ankle studies.